TOUR GUIDE STRATEGIES IN PROMOTING INDRAPATRA FORT: STRATEGI PEMANDU WISATA DALAM MEMPROMOSIKAN BENTENG INDRAPATRA - Yulianda, Fikri; Manan, Nuraini A.; Hermansyah (Indonesian Journal of Islamic History and Culture, 2023)
This research examines the strategies employed by tour guides in promoting Indrapatra Fort. The methods used include interviews and observations. The results show that tour guides use strategies such as providing information about the location, creating impressions, and offering the best service, supported by language understood by tourists. The government also plays a part in promoting Indrapatra Fort. However, tour guides differ by employing promotional techniques such as social media publicity, printed media in the form of articles found in newspapers, and fundraising for promotion. In addition to media promotion, the government also establishes relationships with external parties to attract tourists. Regarding the promotion of Indrapatra Fort, it undeniably has an impact on the local community by increasing income and improving the standard of living in the economic sector.